What Keeps Teachers Engaged during Professional Development? The Role of Interest Development - Mete Akcaoglu; Meryem Seyda Ozcan; Selcuk Dogan (MDPI AG, 2023)
Interest influences adults' and young learners' learning in formal and informal contexts. Although interest and interest development frameworks have been used in research on student-learning, they are not used in teacher-focused research, especially as "outcomes" of teacher professional development (PD) activities. In this study, we used interest development as the outcome of PD in computer science (CS) and investigated the factors that influenced teachers' (n = 5) interest development toward CS using various data sources and analysis methods. We found that interest development is (a) varied, (b) influenced by self-relation, knowledge, and affect, (c) associated with reengagement with PD activities, and (d) it can be captured using computational text analysis methods and online log data.